Spontaneous immunological activities in the target tissue of vitiligo-prone Smyth and vitiligo-susceptible Brown lines of chicken - Falcon, Daniel M.; Byrne, Kristen A.; Sales, Marites A.; Erf, Gisela F. (Frontiers in Immunology, 2024)
Vitiligo is an acquired de-pigmentation disorder characterized by the post-natal loss of epidermal melanocytes (pigment-producing cells) resulting in the appearance of white patches in the skin. The Smyth chicken is the only model for vitiligo that shares all the characteristics of the human condition including: spontaneous post-natal loss of epidermal melanocytes, interactions between genetic, environmental and immunological factors, and associations with other autoimmune diseases. In addition, an avian model for vitiligo has the added benefit of an easily accessible target tissue (a growing feather) that allows for the repeated sampling of an individual and thus the continuous monitoring of local immune responses over time. In the current study, we sought to gain a comprehensive understanding of the initiating events leading to expression of vitiligo in growing feathers by monitoring the infiltration of leukocytes and concurrent immunological activities in the target tissue beginning prior to visual onset and continuing throughout disease development. Using a combination of flow cytometry and gene expression analyses, we document a sequence of immunologically significant events, including characteristic rises in infiltrating B and αβ T cells as well as evidence of active leukocyte recruitment and cell-mediated immune activities (CCL19, IFNG, GZMA) leading up to visual vitiligo onset. Examination of growing feathers from vitiligo-susceptible Brown line chickens revealed anti-inflammatory immune activities which may be responsible for preventing vitiligo (IL10, CTLA4, FOXP3). Furthermore, we detected positive correlations between infiltrating T cells and changes in their T cell receptor diversity supporting a T cell-specific immune response. Collectively, these results further support the notion of cell-mediated immune destruction of epidermal melanocytes in the pulp of growing feathers and open new avenues of study in the vitiligo-prone Smyth and vitiligo-susceptible Brown line chickens.